Analysis of the situation and impact of german national minority language teaching in Gödöllő - Kalocsai, Ottó; Kolta, Dóra (Studia Mundi – Economica, 2023)
The study analyses the situation of the German minority in Gödöllő and the possibilities of language education, the added value of teaching in the national minority language for children, the impact of national minority language education on attitudes towards language learning and further education, the feeling of belonging to the national minority, and the sense of national community. The impact of the socialisation environment at home, culture and family, language use, will also be analysed. Drawing on the literature, we will review the historical and legislative background, the language use of Germans in Hungary, and the guidelines for national minority schooling. The study is based on a presentation of the German national minority language teaching at the Petőfi Sándor Primary School in Gödöllő. Based on this, an online questionnaire survey was carried out, in which 105 pupils (36 national minority language speakers and 69 non-national minority language speakers) were interviewed, focusing on the links between language socialisation and mother tongue education. The results from the questionnaires were processed using SPSS and Microsoft Excel.